Predictors of Methicillin-resistant Staphylococcus aureus infection in children with acute osteomyelitis - Kang Wang; Chen Wang; Hua Zhu; Yan Zou; Yanhua Feng; Fang Zhang; Yi Qu; Yiren Tian (BMC, 2024)
Abstract Background This study aims to identify risk factors associated with Methicillin-resistant Staphylococcus aureus (MRSA) infection in children diagnosed with acute osteomyelitis (AO) and to elucidate the laboratory characteristics of these MRSA-infected children to enhance early targeted therapeutic interventions. Methods We conducted a retrospective analysis involving 123 children with acute osteomyelitis treated at our hospital. Upon admission, we measured white blood cell (WBC) counts, C-reactive protein (CRP) levels, erythrocyte sedimentation rates (ESR), and platelet counts. Patients were categorized into two groups: the non-MRSA group (n = 73) and the MRSA group (n = 50), with values assigned as follows (non-MRSA group = 0, MRSA group = 1). Results The MRSA group had a significantly higher average age compared to the non-MRSA group (P < 0.05). Notably, the incidence of suppurative arthritis was significantly lower in the MRSA group (P < 0.05). At the time of admission, CRP levels in the MRSA group were markedly elevated compared to those in the non-MRSA group (P < 0.01). After three days of empirical therapy, both WBC and CRP levels remained significantly higher in the MRSA group compared to the non-MRSA group (P < 0.05). Conclusions In children newly admitted with acute osteomyelitis, a CRP level exceeding 73.23 µg/mL may indicate a high likelihood of MRSA infection. For children with AO who have been hospitalized for three days on empirical therapy, the presence of WBC > 10.95 × 10^9/L, CRP > 49.56 µg/mL, age > 3.5 years, and the absence of suppurative arthritis suggests a heightened risk of MRSA infection.